Nanoparticles and capillary electrophoresis: A marriage with environmental impact. Issue 15 (27th June 2016) - Mebert, Andrea Mathilde; Tuttolomondo, Maria Victoria; Echazú, Maria Inés Alvarez; Foglia, Maria Lucia; Alvarez, Gisela Solange; Vescina, María Cristina; Santo‐Orihuela, Pablo Luis; Desimone, Martín Federico
Abstract : The impact of nanomaterials in the environment and human health is a cause of big concern and even though intensive studies are currently being carried out, there is still a lot to elucidate. The development of validated methods for the characterization and quantification of nanomaterials and their impact on the environment should be encouraged to achieve a proper, safe, and sustainable use of nanoparticles (NPs). Recently, CE emerged as a well‐adapted technique for the analysis of environmental samples. This review presents the application of NPs together with CE systems for environmental pollutants analysis, as well as the application of CE techniques for the analysis of various types of NPs.